2009
DOI: 10.1182/blood-2008-09-179507
|View full text |Cite
|
Sign up to set email alerts
|

IFN-λ1 (IL-29) inhibits GATA3 expression and suppresses Th2 responses in human naive and memory T cells

Abstract: IFN-1 (IL-29

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
119
1
8

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(134 citation statements)
references
References 54 publications
6
119
1
8
Order By: Relevance
“…In contrast to these investigations, some studies did propose direct effects of IFN-ls on monocytes, 32,33 DCs 34 and T cells. [35][36][37][38][39][40] We currently cannot explain the discrepancy in these observations in terms of whether IFN-ls influence, for example, monocytes or T cells. As we demonstrated, it seems that the preactivation with cell-specific stimuli or virus-mimicking agents could not confer any clear responsiveness to these cytokines on peripheral immune cells.…”
Section: Discussionmentioning
confidence: 94%
“…In contrast to these investigations, some studies did propose direct effects of IFN-ls on monocytes, 32,33 DCs 34 and T cells. [35][36][37][38][39][40] We currently cannot explain the discrepancy in these observations in terms of whether IFN-ls influence, for example, monocytes or T cells. As we demonstrated, it seems that the preactivation with cell-specific stimuli or virus-mimicking agents could not confer any clear responsiveness to these cytokines on peripheral immune cells.…”
Section: Discussionmentioning
confidence: 94%
“…IL-29, expressed together with IFN-a by pDCs and macrophages in response to TLR ligands, was irrelevant in this process, despite its claimed role in T H 2 regulation. 33 We then decided to investigate the possible in vivo effects of nDer p 2-Conj in a murine prophylactic model of respiratory allergy aimed to assess the possible pro-T H 1 activity of the preparation. In nDer p 2-Conj-sensitized mice, IL-13 expression was decreased in the lungs and in in vitro allergen-stimulated, lungisolated mononuclear cells, suggesting a prevalent effect on the adaptive response.…”
Section: Discussionmentioning
confidence: 99%
“…These effects can be direct on CD4 + T cells or indirect, via MDDC. Further, IFN-l1 secretion is itself Th2 cytokine responsive (11,12,(21)(22)(23). Recent studies also showed that IFN-l1 expression is reduced in alveolar macrophages and bronchial epithelial cells of rhinovirus-infected asthmatic individuals (24,25).…”
mentioning
confidence: 99%
“…Expression of IFN-l is restricted mainly to plasmacytoid dendritic cells and epithelial cells (8,9). Furthermore, expression of the IFN-l receptor (in which both chains are distinct from those used in either the type I or type II IFNRs) is almost completely restricted to immune cells and epithelial cells (9)(10)(11)(12). Thus, the restricted expression pattern of the IFN-l ligands and their receptor confers tight control on IFN-l responsiveness, in contrast to the situation with the ubiquitous type I IFNs.…”
mentioning
confidence: 99%
See 1 more Smart Citation